A novel tool to screen for treatments with clenbuterol in bovine: Identification of two hepatic markers by metabolomics investigation. (15th August 2021) - Stella, Roberto; Bovo, Davide; Mastrorilli, Eleonora; Manuali, Elisabetta; Pezzolato, Marzia; Bozzetta, Elena; Lega, Francesca; Angeletti, Roberto; Biancotto, Giancarlo
Highlights: Metabolomics analysis underscored markers of clenbuterol administration. Clenbuterol administration affect metabolic pathways in liver. Quantification of liver metabolites indirectly reveal clenbuterol administration. A diagnostic tool to detect abuse of clenbuterol was developed and validated. Abstract: Surveillance of illegal use of growth promoters such as β2 -agonists in food producing animals rely on the detection of drug residues by LC-MS/MS. Screening strategies focusing on indirect physiological responses following administration of active compounds are promising approaches to strengthen existing targeted methods and ensure food safety. A metabolomics analysis based on LC-HRMS was carried out on liver extracts from bulls experimentally treated with clenbuterol combined with dexamethasone (n = 8) to mimic a potential anabolic practice, and control animals (n = 8). Nicotinic acid and 5′-deoxy-5′-methylthioadenosine were identified as biomarkers of treatment. Ratio values of such markers to others of the same metabolic pathways (nicotinamide or methionine) were used to develop a classification model to assign animals as treated with clenbuterol or non-treated. The classification model was tested on an external validation set comprising 74 animals either treated with different anabolic compounds (β2 -agonists, sexual steroids, corticosteroid), or non-treated, showing 100% sensitivity and specificity.